Sémantisme et potentiel argumentatif des dérivés dénominaux en anti- - Franziska Heyna (Discours)
The aim of this study is to examine antiN derivatives from a semantic and a pragmatic point of view, especially as far as argumentative possibilities are concerned. Two types of derivatives can be distinguished depending on the semantic content of the prefix: anti takes an adversative meaning in anti1N derivatives (eg. anti-rides, antigrippe) and an antonymous meaning in anti2N derivatives (eg. antihéros, antiroman). It will be shown that the interpretation of the antiN derivative is closely related to the syntactic contexts in which it figures. For the anti1N derivatives, the ontological category of will be examined (intensional or intensional object, “attracteur” (Berrendonner 1990), etc.). Within a corpus-based approach, it will be argued that the under-specification of might account for the argumentative potential of the anti1N derivatives. For the second type of derivatives, i.e. anti2N derivatives, the antonymic relation will be more clearly defined. Finally, a hypothesis about the internal structure of the two types will be made.